Phase evolution, powder morphology and photoluminescence exploration of borohydride derived red-emitting Eu3+-doped ZnO nanophosphors. (October 2021) - Singh, Rahul; King, Abhishek; Nayak, Bibhuti B.
Abstract: Deep red-emitting Eu 3+ -doped ZnO nanostructured materials were successfully prepared considering three different zinc-based precursor salts such as acetate, chloride and nitrate using sodium borohydride. XRD results confirmed the presence of ZnO at 800 °C for all samples. However, the nucleation of impurity phases such as EuBO3 and Eu(BO2 )3 were significantly evolved and partly crystalline in nature while using nitrate precursor. When the samples were prepared by acetate and chloride precursors, the nucleation of impurity phases were not properly crystallized. The FTIR analysis confirmed the presence of metal-oxygen bond (M-O), triangular borate (BO3 ), tetrahedral borate (BO4 ) and hydroxyl (O–H/B–OH) groups, and thus it helps to form ZnO along with impurity phases. Flower-like morphology along with polyhedral particles was observed for acetate-based sample. In addition, polyhedral and elongated/elliptical shaped particles were found in nitrate and chloride precursor based samples. The Raman spectra suggested the presence of defects such as oxygen vacancy, zinc related defects, and their complexes in all the samples. Emission spectra for all samples exhibit a broad red emission at 613 nm, which corresponds to the electric dipole 5 D0 → 7 F2 transition. However, a splitting shoulder peak was significantly observed in the 5 D0 → 7 F2 transition for the sample prepared by nitrate precursor, and it was attributed to the existence of impurity phases. Moreover, the impurity phases were not evolved for the sample prepared by chloride and nitrate precursor, and thus the shoulder peak was not considerably noticeable. The presence of impurity phases in nitrate-based samples does not hamper but moderately enhanced the photoluminescence characteristics. The luminescence decay curve was well fitted with the bi-exponential function, and it suggested that the dopant ions have located in two different environments. The quantum yield of acetate-based sample was found to be 3.56%. Further, the results of asymmetric ratio, CIE coordinates and colour purity suggested that the samples can be used in red-emitting indoor lighting application. Graphical abstract: Image 1 Highlights: Deep red-emitting Eu 3+ -doped ZnO have been prepared using NaBH4 and Zn-based salts. The minor EuBO3 and Eu(BO2 )3 are impurity in the ZnO host. Nature of Zn-salts and counter ions influence on the morphology of Eu 3+ -doped ZnO. Presence of impurity phases moderately improve the PL characteristics.